Glycosylated Hemoglobin A1c Is Associated with Anthropometric Measurements and Tumor Characteristics in Breast Cancer Patients - Ayoub NM; Jaradat SK; Alhusban A; Tahaineh L (Dove Medical Press, 2020)
Nehad M Ayoub, Sara K Jaradat, Ahmed Alhusban, Linda Tahaineh Department of Clinical Pharmacy, Faculty of Pharmacy, Jordan University of Science and Technology (JUST), Irbid, JordanCorrespondence: Nehad M AyoubDepartment of Clinical Pharmacy, Faculty of Pharmacy, Jordan University of Science and Technology (JUST), P.O. Box 3030, Irbid 22110, JordanTel +962 27201000 Ext 23809Fax +962 27095123Email nmayoub@just.edu.joPurpose: To investigate the association between glycosylated hemoglobin A1c (HbA1c) with anthropometric measurements and clinicopathologic characteristics of breast cancer patients. Such data are lacking in Arabian countries.Patients and Methods: A cross-sectional study was conducted at the Outpatient Oncology Unit at King Hussein Medical Center at the Royal Medical Services (RMS) and 223 breast cancer patients were included. Blood levels of HbA1c were measured and patients were classified into normal/non-diabetic (HbA1c < 5.7%), prediabetic (HbA1c 5.7– 6.4%), and diabetic (HbA1c ≥ 6.5%).Results: The average age of patients was 49.9± 10.3 years. Most patients had waist circumference equal to or more than 80 cm (91.9%) and more than half (55.2%) had waist-hip ratio equal to or more than 0.85. Mean body mass index (BMI) was 29.9± 5.7 kg/m2. The mean level of HbA1c was 6.2± 1.4% (range 4.7% to 12.6%). HbA1c levels revealed that most patients in this study classified as prediabetics (44.4%). There was a significant positive correlation between HbA1c levels and each of patient’s age (r=0.267, p< 0.001), waist circumference (r=0.180, p=0.008), and waist-hip ratio (r=0.278, p< 0.001). Compared with premenopausal breast cancer patients, postmenopausal patients had significantly higher HbA1c blood levels (t=– 3.542, p=0.003). HbA1c was significantly associated with stage (p=0.044) and grade (p=0.016) of carcinoma in premenopausal breast cancer patients. Among postmenopausal cases, HbA1c was significantly associated with molecular subtype of the disease (p=0.039).Conclusion: The majority of Jordanian breast cancer patients in this study are prediabetic, obese, and had visceral obesity. HbA1c levels are increased among older patients and those who have greater waist circumference and waist-hip ratio. HbA1c is associated with advanced stage and grade of breast carcinoma in premenopausal patients and with molecular subtype in postmenopausal cases. These findings urge the need to screen breast cancer patients for glycemic status upon disease presentation and to further consider treatments to control hyperglycemia in order to reduce the impact of metabolic derangements on disease prognosis and outcomes.Keywords: breast cancer, glycosylated hemoglobin, clinicopathologic, prediabetes